2017
DOI: 10.4085/1062-6050-52.3.06
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in High School Athletes' Knowledge of Sport-Related Concussion Symptoms and Reporting Behaviors

Abstract: Context: Recent researchers have reported that athletes' knowledge of sport-related concussion (SRC) has increased but that athletes still lack knowledge of all the signs and symptoms of SRC. Understanding the signs and symptoms of SRC and the dangers of playing while symptomatic are critical to reporting behaviors in high school athletes.Objective: To examine sex differences in knowledge of SRC symptoms and reasons for not reporting a suspected SRC to an authoritative figure in high school athletes.Design: Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 33 publications
6
101
6
Order By: Relevance
“…Therefore, the opportunity for improvement via educational outreach remains, especially with male athletes, as they were less likely to report symptoms than females. 19 Yet despite recent educational and awareness efforts, some athletes or coaches with certain personal attributes prioritize competitiveness and success over anything else. Outreach must extend beyond knowledge to improve effectiveness because increasing knowledge alone may not provoke behavior change.…”
Section: Discussion Education Efforts Appeared To Be Only Modestly Efmentioning
confidence: 99%
“…Therefore, the opportunity for improvement via educational outreach remains, especially with male athletes, as they were less likely to report symptoms than females. 19 Yet despite recent educational and awareness efforts, some athletes or coaches with certain personal attributes prioritize competitiveness and success over anything else. Outreach must extend beyond knowledge to improve effectiveness because increasing knowledge alone may not provoke behavior change.…”
Section: Discussion Education Efforts Appeared To Be Only Modestly Efmentioning
confidence: 99%
“…33,34 In high school and collegiate cohorts, young women in sex-comparable sports (eg, girls' versus boys' soccer) were more likely to disclose symptoms compared with their male counterparts. 18,35 This may be a result of improved concussion-related knowledge and attitudes, the inherent characteristics of sports, or additional unknown factors. Our findings suggest that sportspecific educational messaging is indicated, specifically concerning symptom identification in youth ice hockey players.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, we need to understand key intrapersonallevel factors in youth sports, such as the athlete's age, history of concussion, and exposure to concussion education. These factors may play roles in high school and collegiate athletes' [15][16][17][18][19] concussion-related knowledge and behaviors, with older athletes having better knowledge and those with a concussion history displaying no difference in knowledge. However, public health investigators 20 have observed that previous experience with other conditions influences the responses to subsequent experiences with that condition.…”
mentioning
confidence: 99%
“…30 A third factor may be related to the distribution of male versus female athletes. In a recent study, Wallace et al 37 reported that males were much less likely to report an SRC than females. The percentage of males was indeed higher in the LoAT group than in the HiAT group, but the percentage of males was similar between the LoAT and MidAT schools.…”
Section: Discussionmentioning
confidence: 97%